Radikalisme Agama dalam Pemberitaan Media Massa: Analisis Framing dengan pendekatan Dakwah - Halimatus, Nur (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2023)
Religious radicalism is a parasite for the state if its radical implementation is expressed externally, the rise of radical understandings circulating slowly ravages the integrity of the state, especially movements carried out in the name of Islam, which then becomes a big homework for the existence and vision and mission of Islam, because clashes with the concept of rahmatanlilalamin, the method used in this study is qualitative interpretive, referring to written sources with a focus on observing the Kompas.com news on May 27 2022, using framing analysis we can find out the role and alignment of the mass media on this issue, and the results is that the mass media side with the government is also a vehicle for da'wah in counteracting this radicalism, viewed through the lens of da'wah trying to see the harmony of Islamic da'wah and this movement of religious radicalism. The application of da'wah under the pretext of achieving the goals of da'wah in no way justifies rebellion against government authority as long as it does not conflict with the ushul's beliefs and teachings. The line of da'wah still refers to amar makruf nahi mungkar, the two will go hand in hand and will automatically run like that, apart from that the demands of da'wah race on Allah's commands in surah An-Nahl 125: da'wah with wisdom, mauidzah hasanah, and mujadalah bil ihsan.